The aesthetic factor as a formative element in industrial design, from the aspect of industrial aesthetics in the fashion industry - Efremov Jordan; Kertakova Marija; Dimitrijeva-Kuzmanovska Vangja (Tekstilna industrija, 2023)
Formative elements of industrial design, i.e. design factors, represent components of its content, where together with the form of the design, they form an indivisible whole. Besides the aesthetic component, the other formative elements are not visually precisely defined, therefore an analysis is needed to determine their value. In the modern science and theory of industrial design, new knowledge and changes are constantly incorporated into the essence, in the value and in the meaning of certain formative elements of industrial design, where the interdisciplinary approach in creative activity is emphasized. With the development of mass production and consumption, the satisfaction of aesthetic factors in industrial design has an increasing importance. Also, with the development of the social standard and the general culture, the need for the design to be more and more attractive automatically opened up. The aesthetic characteristics that are most acceptable to people are: Compliance of the form, harmony, proportions of the dimensions, the unity of the product, the choice of color etc. Styling - Styling indicates the way in which something is made, designed or executed. Styling is a method and direction in design, in which designers impose inappropriate shapes on certain products, thus, in an unnatural or artificial way, they try to only seemingly change the shape of the objects, in order to get the impression that it is a new product. Fashion is a collective social phenomenon, but when it comes to industrial design, it is short-lived. It has a growing importance for certain categories in industrial design and is used as a tool for successful design. The influence and significance of fashion in industrial design cannot be neglected and has a decisive influence on the placement, and therefore on the existence of producers.